MENEROPONG MADRASAH DALAM BINGKAI STANDAR NASIONAL PENDIDIKAN - Zakiyah Kholidah (Al Hikmah: Jurnal Studi Keislaman, 2014)
Abstract: Education is a process of interaction aimed at improving the quality of human resources, the entire education in Indonesia organized both structurally and not structurally is the responsibility of the Ministry of National Education regulated through legislation. Law of the national education system can serve as a milestone and a basis to build a better quality of national education, including the pattern of national development management. Various attempts have been attempted to improve the quality of madrasah education, the madrasah (Islamic schools) have still experienced many problems and obstacles that hinder the development and improvement of the quality of madrasah. The quality of education is not a stand-alone concept but is closely related to the demands of society that continue to move towards the future. Demands to improve the quality of education affect all sectors and have inevitably become the need that can must immediately be adderessed. There are many efforts to improve the quality of madrasah education for example by improving the quality of madrasah resources, managing madrasah governance to be effective and efficient, and increasing the role of the madrasah leader. To overcome the problems of madrasah there should be reviews of the vision, mission, commitment and institutional management periodically in accordance with the development of science and the demands of society.